Investigating different factors influencing women’s economic activities - Mohammad Javad Ghasemi (Management Science Letters)
There are many studies on how to share women’s involvement in economic activities and what sectors of industries could contribute more to their job involvement. This paper presents an empirical investigation to learn how economic growth in service industry, agricultural industry as well as other industries could contribute on economic growth. The study uses vector error correction to study the relationship between value added and women’s job opportunities in Iran over the period 1951-2003. In industrial sector, the results of the survey indicate that an increase of one percent on growth domestic product (GDP) and wage increases 4.47% and reduces 1.95 % of women’s employment, respectively. In addition, an increase of one percent on GDP and wage increases 0.24% and reduces 0.25 % of women’s employment in service industry, respectively. Finally, an increase of one percent in GDP increases wage by 4.47% and reduces women’s employment by 1.95%, respectively.